BALANCING HOST STATE SOVEREIGNTY AND FOREIGN INVESTORS’ RIGHTS THROUGH A MINING DIVESTMENT RULE - Tamara Sulistio, Chealse; Trisnamansyah, Purnama (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2020)
ABSTRACTShare divestment in foreign mining has been a significant focus for the Indonesian Government as its purpose to reverted national sovereignty through the state-control over natural resources and attempt to gain direct access to profits of the multinational companies through an ownership stake. Under Law No. 4 of 2009 on Mineral and Coal Mining (Mining Law), all foreign companies in mining are required to divest 51 percent of their interest in stage to the national participant. The State has indeed the right to protect its economy as a manifestation of permanent sovereignty. In an age of globalization, however, it is also necessary to maintaining their external sovereignty rights, including the right to establish relationships outside. This research aims to examine the implementation of shares divestment scheme in Mining Law to host state sovereignty. The method used is normative legal research and specification of descriptive analysis. The finding shows that the intention of the divestment obligation challenging to attain due to the process of the implementation of the divestment obligation is not in line with the fundamental principles of investment law and the concept of international economic sovereignty of Indonesia. The main goal of which is to devise series of recommendations and whether the alternative solution based on the other countries’ experience, which expected will be applied to reduce the risk for both host state and foreign investors in the mining sector.Keywords: Share Divestment, Mining Law, Sovereignty, Foreign Investment